University of Washington Institute for Simulation and Interprofessional Studies Curriculum for Flexible Bronchoscopy - Carrie Chun; Mark Tonelli; Sara Kim; Megan Sherman (Association of American Medical Colleges, 2010)
Abstract Introduction At the University of Washington, first-year fellows were typically given cognitive training on FB during an orientation course. However, hands-on training was limited to practicing airway navigation with a fiberoptic bronchoscope and plastic bronchial tree model. In an effort to provide a more realistic hands-on training experience, we introduced high-fidelity simulation-based curriculum in fiberoptic flexible bronchoscopy (FB) to our orientation course for pulmonary and critical care medicine fellows in training. Methods Through a didactic lecture, learners are introduced to the history of and theory behind FB, clinical indications and contraindications to FB (including risk/benefit information that should be used to obtain informed consent from patients), and lung and bronchial tree anatomy. Learners then have an opportunity to review airway anatomy and practice bronchoscope maneuvers (i.e., airway inspection and bronchoalveolar lavage) on a high-fidelity bronchoscopy simulator (Immersion Medical Endoscopy AccuTouch). Results This curriculum was launched during the 2007-2008 academic year. It was well received by the participating eight fellows with six reporting that the simulation was very realistic and two reporting that the simulation was somewhat realistic. All eight fellows thought the training was very helpful. Using a Likert scale (1 = very uncomfortable, 5 = very comfortable) to rate confidence in bronchoscopy skills, the average pretraining confidence level increased from 1.9 pretraining to 3.5 posttraining. Faculty physicians were also surveyed during this inaugural year, and 89% of respondents thought bronchoscopy simulator training should be a required component of the fellow curriculum. Discussion Simulation technology has been shown to improve skills training. Use of a high-fidelity bronchoscopy simulator allows for an introduction to airway anatomy and basic bronchoscopic skills in a safe, nonthreatening environment. It provides trainees with the opportunity to practice the procedures without the risk of harm to patients. Simulation technology also offers the ability to conduct a structured assessment of trainee competence of this important procedural skill.